Strategic Satisficing? A Behavioral-Agency Theory Perspective on Stock Repurchase Program Announcements - Sanders, Wm. Gerard; Carpenter, Mason A. (Academy of Management Journal, 2003)
Executives confront potentially conflicting pressures?maximizing shareholder wealth in the long term and appeasing shareholders in the near term. Because they must address near-term pressures to preserve tenure and to realize the benefits of long-term strategies, executives are increasingly likely to seek to mollify shareholders. We develop a behavioral-agency theoretical framework for studying how stock repurchase programs are used to help top managers appease shareholders. Analysts of 250 large U.S. firms suggested that stock repurchase programs are variously a function of information asymmetry, risky stock-based incentives, and performance expectations.